Modeling and Control of an Ill-Conditioned Distillation Column - Vu, Trieu Minh; Idris, Bin Ibrahim (ACTA Press, 2010)
This paper briefly introduces a theoretical calculation procedure for modeling and simulation of a distillation process based on the energy balance method. The mathematical modeling is developed over three steps: the basic nonlinear model, the full-order linearized model and the reduced-order linear model. The reduced-order linear model is then used as a regulator for a model predictive control (MPC) to verify the ability of a conventional MPC controller that satisfies the output specifications subject to the input constraints. A modified MPC controller for ill-conditioned process with output regions is developed to improve the robustness of the controller for handling the input and output constraints and rejecting disturbances. Compared with the traditional method of MPC for an ill-conditioned process that deletes some controlled variables, the modified method with output regions proves its superiority because it still maintains penalty on the output deviation from the desired region into its controlled objective function.